Olhar, ouvir e escrever: uma etnografia em grupos de pesquisa da Educação Física brasileira - Consoli, Daniela de Almeida (2020)
Understanding the scientific communication process of research groups, especially those linked to Universities, has been pointed out by several authors as relevant (HOLLIS, 2001; ACEDO et al., 2006; MAUTHNER; DOUCET, 2008; ODELIUS et al., 2011 ), by enabl